A preparação do ator e o método pilates: algumas ressignificações à luz das diretrizes somáticas - Almeida, Sâmara Batista (2022)
The Pilates Method was created by Joseph H. Pilates who called it “Contrology”. It is a term that is used to refer to the conscious control of all body movements, providing the connection between body and mind. Its development was based on anatomical, physiological and philosophical studies. In this context, the present research aims to investigate a pedagogical proposal that uses physiotherapy as a support tool for the actor's work and uses the Pilates Method as a basis to develop body awareness. Based on the pedagogy of the Somatic Guidelines, we seek to enable the creation of activities and exercises aimed at body knowledge in the Performing Arts. In this way, we propose a process of creating short scenes so that the Performing Arts practitioners can have a greater knowledge, perception and exploration of their own body as well as their "self", observing the development of the actor's body on stage, through the deepening of the different movements inspired by Pilates. In the investigation construction process, actors training sequences recorded in videos were used as exercises, paintings and photographs as a basis for creation aligned with the methodology of corporeal mimesis, aiming to stimulate the student to discover different movements from those performed in their daily lives, expanding their perception of the body in communication. The movements inspired by the Pilates Method contributed to the development of body awareness by working the body in its internal structure. The findings of this study in a teaching internship format are consistent with the results of other research on the development of body awareness in the Performing Arts. The technique of qualitative approach to the material was based on the appreciation of the observations made in the classroom, using as a selection criterion the proposal of the course syllabus taught in the teaching internship. The methodology used to analyze the material collected was Bardin's Content Analysis (2000). The way to collect the data was through the transcription of the practices, the transcription of interviews with the participants, and the notes in the Field Diary, from the methodological procedures that were carried out through a case study with students of the discipline CorpoVoz IV. at the Federal University of Uberlândia (UFU). We seek, however. not to interfere in the way the students positioned themselves by making a spontaneous writing based on the spelling proposal made by Hartmann (2011). The collected data show that as for the Somatic Guidelines, the Pilates Method contributes to the integration of anatomy and body awareness, through specific activities that provide references for the expression of the body.